Paratradução: uma prática editorial e um caso de Machado de Assis em espanhol - Juliana Aparecida Gimenes (Hermeneus, 2021)
In this paper, we proposed a reading of paratexts (Genette, 2009) in two translations of Memórias póstumas de Brás Cubas into Spanish, in order to analyze the way Machado de Assis’ image is constructed. As a critical approach of working with the translated texts, paratranslation allows us to understand not only the wider aspects regarding the text itself, but also those related to the translation process within the editorial practices (Yuste Frías, 2011, 2015). We have recognized an emphasis on the biographical aspects of Machado de Assis, mainly about his childhood as a poor black boy in 1800’s Brazil as well as his adulthood as a literary genius and an epileptic person. We have also compared this construction of Machado as an author, the more well-known and repeated image along the years, with another Machadopresented by Massa (2009a).